New insight regarding mode of action of brown rot decay of modified wood based on DNA and gene expression studies: a review. (February 2015) - Alfredsen, G.; Ringman, R.; Pilgård, A.; Fossdal, C. G.
Abstract : Modified wood shows resistance against wood deteriorating fungi, but the mechanisms are still not fully understood. The aim of this paper was to summarise the molecular studies performed on modified wood with regard to brown rot decay fungi. The DNA data showed that fungi are present inside the laboratory wood test samples already after two weeks of inoculation. Generally the fungal DNA content reflects mass loss and wood moisture content. The oxidative gene expression seems to be higher in modified wood than in untreated wood and it tend to increase during incubation. Based on the gene expression data we suggest that the hypothesis of lack of substrate recognition by the fungus should be rejected. In the reviewed studies, total wood moisture content in the samples was generally not low enough to inhibit fungal colonisation. Hence, moisture distribution within the wood should be studied more closely.